1982
DOI: 10.1017/s0022112082001293
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Reynolds stresses and the mean-flow field in a three-dimensional pressure-driven boundary layer

Abstract: An experimental study of a steady, incompressible, three-dimensional turbulent boundary layer approaching separation is reported. The flow field external to the boundary layer was deflected laterally by turning vanes so that streamwise flow deceleration occurred simultaneous with cross-flow acceleration. At 21 stations profiles of the mean-velocity components and of the six Reynolds stresses were measured with single- and X-hot-wire probes, which were rotatable around their longitudinal axes. The calibration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Detailed comparisons presented in Anderson & Eaton (1987) show that the data a t station 5 compare well with the data of Dechow & Felsch (1977) and plots. Muller (1982). Both of these flows are 'obstacle-type' flows where the initially twodimensional boundary layer is deflected sideways by an obstacle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed comparisons presented in Anderson & Eaton (1987) show that the data a t station 5 compare well with the data of Dechow & Felsch (1977) and plots. Muller (1982). Both of these flows are 'obstacle-type' flows where the initially twodimensional boundary layer is deflected sideways by an obstacle.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments in somewhat more complicated geomet,ries have arrived at different conclusions. For example, Ezekwe Pierce & McAllister (1978), Fernholz & Vagt (1981), and Muller (1982) have all observed a lead in the shear stress vector ahead of the strain rate. Fernholz & Vagt (1981) concluded that this was caused by very rapid distortions of the turbulence.…”
Section: Reynolds Stress Development In Turbulent Boundary Layers 265mentioning
confidence: 99%
“…They measured only mean flow and wall shear stress, and noted that the mean velocity appeared to be turning all the way to the wall. Müller (1982) measured flow turned spanwise by vanes, in a geometry similar to the current experiment.…”
Section: Post-1976 Experimentsmentioning
confidence: 91%
“…The hot-wire response equations were developed incorporating corrections for the tangential and normal sensitivity coefficients, k and h, respectively and were similar to Ref. [33,34]. The k and h corrections for the probe were obtained from the calibration of the probes in two planes.…”
Section: Experimental Methodsmentioning
confidence: 99%